Economic performance of dairy goat farming in Greece. Preliminary results - Batzios A.; Theodoridis A.; Bournaris T.; Semos A. (Pastoralism and sustainable development: proceedings, 2021)
The aim of this study is to outline the main technical and economic indicators of dairy goat sector in Greece. Through face-to-face interviews with farmers detailed accounting data were collected from 96 goat farms located in Northern Greece and a comparative analysis was carried out using milk yield/doe and farm size as classification criteria. Analysis showed that the farm indicators vary considerably, both in terms of milk yield and farm size. Milk production/doe is 155.17 kg for average farm, while in small size farms is considerably higher compared to medium and large size farms. The average farm uses 18.59 hours of labor/doe, of which 29.7% is hired labor. Small size farm uses more labor/doe, followed by medium and large size farm. Milk yield and farm size are both associated with the composition of the labor used,confirming that hired labor is more important in high milk yield and large size farms. Low milk yield farm pays less rent for land/doe than high milk yield farm, while farm size is negatively associated to land rent. High differences exist both among milk yield groups and among farm size groups regarding the composition of labor cost. Milk yield and farm size are also negatively related to the variable cost, fixed capital cost, and total production cost. In general goat farms exhibit losses, although the economic performance of the farms is improved as the milk yield and the size of the farm are increasing. The findings of this study could be useful for a more rational management towards increasing the productivity and enhancing the competitiveness of goat farming.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)